2012
DOI: 10.1016/j.neuroimage.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of numbers and mathematical terms

Abstract: Numerical processing has been demonstrated to be subserved typically by the brain regions around the bilateral intraparietal sulcus (IPS). The goal of the current study was to investigate whether the processing of mathematical terms shared the same brain regions with numerical processing. Healthy adult participants performed semantic distance judgment tasks on five types of materials, including geometric terms, algebraic terms, linguistic terms, words for tools and other common objects, and Arabic numbers. Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 92 publications
5
35
0
Order By: Relevance
“…These regions include linguistic regions STS and STG extending to the temporal poles, and DMN regions including PMC, mPFC, and dlPFC. However, unlike during narrative storytelling, and in accordance with the scientific nature of our lecture, we also observed teacher-student alignment in bilateral SPL, which has been implicated in mental rotation, geometry, and mathematical symbols (Gogos et al, 2010;Prescott et al, 2010;Zhang et al, 2012;Harvey et al, 2013), as well as the manipulation and rearrangement of information in working memory (Koenigs et al, 2009). We also do not observe teacher-student coupling in bilateral TPJ, a region of the brain that is strongly implicated in mentalizing and theory of mind (Saxe and Kanwisher, 2003;Schilbach et al, 2008;Mars et al, 2012), suggesting that aspects of speaker-listener coupling are content-specific.…”
Section: Discussionsupporting
confidence: 84%
“…These regions include linguistic regions STS and STG extending to the temporal poles, and DMN regions including PMC, mPFC, and dlPFC. However, unlike during narrative storytelling, and in accordance with the scientific nature of our lecture, we also observed teacher-student alignment in bilateral SPL, which has been implicated in mental rotation, geometry, and mathematical symbols (Gogos et al, 2010;Prescott et al, 2010;Zhang et al, 2012;Harvey et al, 2013), as well as the manipulation and rearrangement of information in working memory (Koenigs et al, 2009). We also do not observe teacher-student coupling in bilateral TPJ, a region of the brain that is strongly implicated in mentalizing and theory of mind (Saxe and Kanwisher, 2003;Schilbach et al, 2008;Mars et al, 2012), suggesting that aspects of speaker-listener coupling are content-specific.…”
Section: Discussionsupporting
confidence: 84%
“…For example, the anterior IPS is assumed to play a crucial role in cognitive representation of numerical quantities (Dehaene et al, 2003; Zhang et al, 2012). A recently published meta-analysis study showed that number and calculation tasks elicited activity in such region as the inferior parietal lobule (Arsalidou and Taylor, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The IPL is known to be involved in the mathematical cognitive processing (Ansari, 2008;Nieder and Dehaene, 2009). The middle IPL, especially cluster 5, responds consistently to mathematical operations (Cohen et al, 2000;Cohen Kadosh et al, 2007;Delazer et al, 2003;Fulbright et al, 2000;Grabner et al, 2009;Kroger et al, 2008;Naccache and Dehaene, 2001;Piazza et al, 2007;Zhang et al, 2012b). On the other hand, the posterior IPL seems involved in the use of learned mathematics, as when comparing trained and untrained conditions (Delazer et al, 2003;Grabner et al, 2009), in contrast to the middle IPL.…”
Section: Zhang and LImentioning
confidence: 99%